Neurohermeneutics A Transdisciplinary Approach to Literature - Gambino Renata; Pulvirenti Grazia (Gestalt Theory, 2019)
In the epistemic frame of the biocultural turn and of the neuroaesthetics, we have developed neurohermeneutics as an approach to literature that aims at contributing to the current debate about the linkage between literary, cognitive and neuroscientific studies, focusing on the relationship between mindbrain processes mirrored in the formal features of the text and the strategies activated by the author in a text in order to guide the reader in imagining, emotionally feeling and cognitively getting meanings out of the literary experience. The aim of the neurohermeneutical approach is to grasp and describe phenomenologically the mirroring process between the two extremes of the literary experience, i.e. the writer’s creative process as it is mirrored in the formal features of the literary work and the reader’s imaginative reconfiguration of the text, and what they share in common. The reader revives the mental imaginative processes of the author by creating his/her unrepeatable individual experiences of the text and subjectively redesigning it in an endless loop of features that trigger the imagination and its creative potential both while writing and by reading literature.